Cost‐minimization analysis comparing intravenous immunoglobulin with plasma exchange in the management of patients with myasthenia gravis. Issue 6 (26th November 2015) - Furlan, Julio C.; Barth, David; Barnett, Carolina; Bril, Vera
ABSTRACT: Introduction: Myasthenia gravis (MG) exacerbations may be treated with intravenous immunoglobulin (IVIg) or plasma exchange (PLEX), which have equivalent effectiveness. This cost‐minimization analysis compared IVIg with PLEX for treatment of patients with MG exacerbation. Methods: We combined the Ontario‐based health cost data with clinical data from a randomized clinical trial. Analyses were undertaken from the perspective of a public healthcare insurer and from the perspective of a tertiary university hospital payer. Results: PLEX was less costly than IVIg among patients with a body mass index (BMI) > 15.7 kg/m 2, from the perspective of the public healthcare insurer ( P < 0.0001). However, PLEX was more costly than IVIg from the perspective of the hospital payer when the costs of blood products were excluded ( P < 0.0001). Conclusions: PLEX can be considered a short‐term cost‐minimizing therapy when compared with IVIg for treatment of MG exacerbation among patients with BMI >15.7 kg/m 2, from the perspective of a public healthcare insurer. Muscle Nerve 53 : 872–876, 2016